6 • 6 • 6
The answer is 6^3
6*6*6= 216
6^3= 216
The given multiplication of 6 • 6 • 6 can be represented using an exponent as 63. The exponent is 3 because the number 6 is being multiplied by itself three times.
In mathematics, the operation of repeated multiplication is often represented using exponents. When you multiply a number by itself repeatedly, the way to express that using exponents is to write the base number and an exponent showing how many times the base number is being multiplied. In your example, you are multiplying 6 by itself 3 times, so the expression that represents this using exponents is 63.
speed of the car have to be to complete the trip in 17 hours?
The speed of car must be 60mile/hour, so that the trip will complete in 17 hours.
The rate of change of position of an object in any direction is called speed.
According to the given question
At a speed of 68 miles per hour, the trip will be complete in 15 hours.
⇒ Total distance covered in 15 hours = 68 × 15 = 1,020 miles
( because, distance = speed × time)
Therefore, the speed of car to complete the trip in 17 hours
=
Hence, the speed of car must be 60mile/hour, so that the trip will complete in 17 hours.
Find out more information about speed, distance and time here:
#SPJ2
Answer:
x = 60
Step-by-step explanation:
t =
15 = k/68
k=1020
~~~~~~~~~~~
17 = 1020/x
x = 1020/17
x = 60
Answer:
a. F'(0, 5), G'(1, 0), H'(-3, 3)
Step-by-step explanation:
Reflection across x = -1 gives you the transformation ...
(x, y) ⇒ (-2 -x, y)
Reflection across y = 1 gives you the transformation ...
(x, y) ⇒ (x, 2 -y)
Together, these give you the transformation ...
(x, y) ⇒ (-2 -x, 2 -y)
Applying this to point F, we have ...
F(-2, -3) ⇒ F'(-2 -(-2), 2 -(-3)) = F'(0, 5) . . . . . . matches choice A
_____
How we found the transformation
In general, if M is the midpoint between A and B, then you have ...
M = (A+B)/2
2M = A+B
B = 2M - A
So, if we want x=-1 to be the midpoint between x' and x, then we have ...
x' = 2(-1) -x = -2 -x
Likewise, if we want y=1 to be the midpoint between y' and y, then we have ...
y' = 2(1) -y = 2 -y
So, the transformation is ...
(x, y) ⇒ (x', y') = (-2 -x, 2 -y)